Pharmacognostical Analysis of Rooibos Leaves - Saxena, Gaurav; Nutan; Rajput, Pallavi (Journal of Drug Delivery and Therapeutics, 2019)
Aspalathus linearis, (Family: Fabaceae) is commonly known as “Rooibos” used mainly due to its antioxidant properties. The study aimed to determine the pharmacognostical standards of “Rooibos” available in the local market. Evaluations were conducted in terms of macroscopic, microscopic, physicochemical and phytochemical analysis according to the WHO and other recommended procedures.Physiochemical investigation of plant for the total ash, acid insoluble ash, water soluble ash,sulphated ash values and loss on drying re 6.26%, 4.0%, 5.46%, 5.66% and 0.30%, respectively. Keywords: Rooibos · Aspalathus linearis, Fabaceae , Rooibos, Pharmacognosy